PENGARUH MOTIVASI BELAJAR DAN PRAKTIK KERJA INDUSTRI TERHADAP KESIAPAN KERJA SISWA KELAS XII SMK BISNIS MANAJEMEN DI KOTA SOLOK - Siti Suryani; Agus Irianto; Efni Cerya (Universitas Negeri Padang, 2018)
Abstract: This study aims to examine the effect of learning motivation and industrial work practices on the work readiness students of class XII in business management vocational schools in Solok city. This reseach is descriptive associative. The population in this study is all students class XII of business management vocational schools in Solok city using primary data and secondary data. The analytical method used is path analysis using the SPSS version 21. The results of this study indicate that:1. Learning motivation has a positive and signifivant effect on Industrial work practices 2. Learning motivation has a positive and significant effect on work readiness 3. Industrial work practices have a positive and significant effect on work readiness Keywords: learning motivation, industrial work practices, work readiness